Effect of Post-Cutting Sugarcane and Sucrose Concentrationon Characteristic Jelly Drink - Albraham Fitrianto; Lukman Hudi (Universitas Muhammadiyah Sidoarjo, 2021)
The aim of this research was to determine effect of post-cutting times and sucrose concentration on the characteristics sugarcane jelly drink used factorial randomized block design. The first factor was post-cutting times (U): 1 day (U1), 3 days (U2), dan 5 days (U3), second factor was sucrose concentration (S): 0% (S1), 5% (S2) dan 10% (S3). The data obtained were then analyzed using analysis of variance and further test BNJ 5%. The results showed there was significant interaction between post-cut sugarcane age and sucrose concentration on the parameters of pH, TPT, reducing sugar, and viscosity of sugarcane jelly drink. The post-cuting times and sucrose concentration was significant affected on the hedonic test of aroma, taste and suction power of sugarcane jelly drink. The best treatment was U1S2 (1 day post-cutting time, 5% sucrose concentration) with characteristics of TPT 14,533 obrix, pH 4.070, reducing sugar 20,370%, viscosity 2,407 x 103 mPa.s, lightness 84,360, and color organoleptic aroma, taste and suction respectively 4,200, 4,567, 3,967 and 4,100.